Pengembangan E-Learning dengan Metode Self Assessment Untuk Meningkatkan Hasil Belajar Matematika Mahasiswa Universitas Mahendradatta - Hignasari, L Virginayoga; Supriadi, Mardiki (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study is aimed to develop e-learning media with self-assessment methods to improve mathematics learning outcomes of college students. The model used in the development of e-learning was the ADDIE model. The sample of this study was 39 college students of the Industrial Engineering Program, Faculty of Engineering, Mahendradatta University. The data analyzed in this study were studentâ€™s mathematics learning outcomes obtained from the posttest scores after using e-learning with self assessment method. To determine the effectiveness of the implementation of e-learning, experimenation with one group pretest and posttest design was conducted. Data of learning outcomes obtained were analyzed by using the Paired T-Test. Based on the results of expert validation and product trials, e-learning was feasible to be implemented. Based on the results of the Paired T-Test, a significant value of less than 0.05 was obtained, so based on the hypothesis that there was a difference between the learning outcomes before and after e-learningÂ was implemented. This was also supported by an increase in the average value of student mathematics learning outcomes, from the initial pretest score of 75,92 to 82,10. Student response value was 69,0 which indicated that the response to e-learning was positive. The increase in learning outcomes was due to e-learning learning with self-assessment methods which provided opportunities for students to increase their confidence in their mathematical skills.